PENGEMBANGAN KEWIRAUSAHAAN BERKELANJUTAN DAN TERPADU DI STITEK BALIK DIWA - Basir, Buana; Kabangnga, Arnold; Saokani, Jawiana; Hidayani, Mesalina Tri; Hamsia, . (Departemen Budidaya Pertanian Fakultas Pertanian UNHAS, 2020)
The underdeveloped entrepreneurial condition at the Balik Diwa Marine Technology College is suspected to be due to the limited business facilities. Moreover, the student mindset is not focused on the benefits of sustainable business independence. High entrepreneurial motivation is defeated by the desire of students to immediately graduate and get a certificate to find work in various agencies. The solution presented by higher education institutions and the Ministry of Research, Technology and Higher Education is to motivate students about the benefits of doing independent and sustainable business activities, by rolling out several student activity programs such as the Student entrepreneurship program, village development grant programs, student creativity programs, integrated learning and work programs, and programs. Entrepreneurial development. The entrepreneurship development program (PPK) is a program that is temporarily run by the Balik Diwa Makassar high school of marine technology which involves students and alumni as tenants. The method used in fostering tenants is through entrepreneurship training, comparative studies, and apprenticeships to small and medium-sized companies, assistance in starting and developing businesses according to their respective competencies, talents, and interests. After going through the selection, training, comparative study, and apprenticeship stages, Tenan seemed to be more enthusiastic with high enthusiasm in starting their respective businesses. There are 12 types of businesses formed from 20 tenants, and more than five types of businesses that have worked from upstream to downstream, starting from the process of pioneering and producing products to marketing. Several types of business, namely Herbal Probiotic (PH) Jolly, Saline to Fresh Ornamental Fish, aquaponic catfish enlargement, crab shell chitosan, seaweed lotion, seaweed crackers /sticks, and LACUBA fishing aid. Keywords: Entrepreneurship program, tenants, business, students. ABSTRAK Kondisi kewirausahaan yang kurang berkembang di Sekolah Tinggi Teknologi Kelautan Balik Diwa diduga karena masih terbatasnya fasilitas usaha dan pola pikir mahasiswa yang kurang terarah terhadap manfaat dari kemandirian usaha yang berkelanjutan. Motivasi wirausaha yang tinggi terkalahkan oleh keinginan mahasiswa untuk segera lulus dan mendapatkan ijazah buat mencari pekerjaan di berbagai instansi. Solusi yang dihadirkan oleh perguruan tinggi dan Kemristek Dikti adalah memberi motivasi kepada mahasiswa tentang manfaat melakukan kegiatan usaha mandiri dan berkelanjutan, dengan menggulirkan beberapa program kegiatan mahasiswa seperti program kewirausahaan mahasiswa, program hibah bina desa, program kreativitas mahasiswa, program belajar dan bekerja terpadu, dan program pengembangan kewirausahaan. Program pengembangan kewirausahaan (PPK) merupakan program yang sementara dijalankan oleh Sekolah Tinggi Teknologi Kelautan Balik Diwa Makassar yang melibatkan mahasiswa dan alumni sebagai tenan. Metode yang digunakan dalam membina tenan yaitu melalui pelatihan kewirausahaan, studi banding dan magang ke perusahaan kecil dan menengah, pendampingan dalam merintis dan mengembangkan usaha sesuai dengan kompetensi, bakat dan minat masing-masing. Setelah melalui tahap seleksi, pelatihan, studi banding dan magang, tenan terlihat lebih antusias dengan semangat yang tinggi dalam merintis usahanya masing-masing. Usaha yang terbentuk sebanyak 12 jenis dari 20 orang tenan, dan lebih dari lima jenis usaha yang sudah berkiprah dari hulu hingga hilir, mulai dari proses merintis dan menghasilkan produk hingga sampai ke pemasaran sudah dilakukan. Beberapa jenis usaha tersebut, yaitu Probiotik Herbal (PH) Jolly, Ikan Hias salin ke tawar, pembesaran lele akuaponik, Kitosan cangkang rajungan, lotion rumput laut, krupuk/stik rumput laut, dan alat bantu tangkap ikan LACUBA. Kata kunci: Program kewirausahaan, tenan, usaha, mahasiswa.